2009
DOI: 10.1111/j.1365-263x.2009.01005.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of inhalation sedation agents in the management of children receiving dental treatment: a randomized, controlled, cross‐over pilot trial

Abstract: The results from this pilot study would suggest no increased benefit, in terms of treatment completion, from the additional use of sevoflurane in combination with nitrous oxide and oxygen. There was, however, a small but significant patient preference in favour of nitrous oxide with sevoflurane and oxygen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
1
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 19 publications
4
26
1
4
Order By: Relevance
“…This compares favourably with the findings of Soldani and co-workers (2010) whilst there were more males in the cohorts studied by other researchers (Bryan 2002;Ashley et al 2010;Soldani et al 2010). …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This compares favourably with the findings of Soldani and co-workers (2010) whilst there were more males in the cohorts studied by other researchers (Bryan 2002;Ashley et al 2010;Soldani et al 2010). …”
Section: Discussionsupporting
confidence: 88%
“…For example, the study by Bryan has commented on the percentage of males and females included in the study population which was 51.2% and 48.8% respectively, but failed to relate any gender differences to treatment outcomes (Bryan 2002). Similarily, the female to male ratio was 3:2 in Soldani and co-workers study, but there was no mention about gender differences based on treatment outcomes (Soldani et al 2010) .…”
Section: Discussionmentioning
confidence: 95%
“…This is in agreement with The only comparative report of N 2 O , sevo IHS for dental treatment (in a sample of 17), reported a satisfactory and reliable success in both two inhalational sedation regimens during third molar surgery [14]. This study's success rates are similar to previously reported N2O IHS success rates and would suggest that the investigators' identification of suitable IHS patients and their management thereafter was at least similar to other workers [5,10,15,24]. This study's success rates are higher for the N 2 O group in contrast to that reported by the Newcastle study (add reference), successful treatment completion was reported for 52% of patients [13].…”
Section: Discussionsupporting
confidence: 82%
“…the differences between the two studies may be due to the longer period of patient assessment in this study , may explain the increased number of minor adverse events in this study [13]. Certainly, the side effects in this study were similar to previous reports, e.g., headache within the 24 h post-N2O IHS in 15% of patients compared with 10% of patients within the same time period in a previous study [15].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation